INTEGRASI ARTIFICIAL INTELLIGENCE DAN ESG DALAM SISTEM EKONOMI MODERN - Hardini Ariningrum; Elsa Fitriandini; Choirunnisa Ramadhani; Tika Rahmawati (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT The rapid development of Artificial Intelligence (AI) has driven significant transformations in accounting systems, particularly in supporting sustainability reporting based on Environmental, Social, and Governance (ESG) principles. However, comprehensive studies that examine the integration of AI and ESG within the context of modern accounting systems remain relatively limited. This study aims to analyze the forms of AI–ESG integration in modern accounting systems and to assess their role in enhancing the quality of corporate sustainability reporting. The study employs a qualitative descriptive approach using a literature review method, analyzing 20 peer-reviewed journal articles published between 2021 and 2025. The literature was sourced from multiple academic databases, including Google Scholar, ScienceDirect, SSRN, and ResearchGate, to ensure comprehensive coverage of relevant studies. Data were analyzed using content analysis, with research findings categorized into key thematic areas related to the application of AI in ESG reporting, carbon and environmental accounting, as well as AI governance and ethical considerations. The results indicate that the integration of AI into accounting systems contributes to improved reporting efficiency, enhanced accuracy and timeliness of sustainability data, and greater transparency of ESG information through automated data collection and processing, risk analysis, and decision-support mechanisms. This study concludes that the integration of AI and ESG expands the role of accounting systems from traditional financial record-keeping tools to strategic instruments that support corporate accountability and long-term sustainability. ABSTRAK Perkembangan kecerdasan buatan (Artificial Intelligence/AI) mendorong transformasi signifikan dalam sistem akuntansi, khususnya dalam mendukung pelaporan keberlanjutan berbasis Environmental, Social, and Governance (ESG). Meskipun demikian, kajian yang membahas integrasi AI dan ESG secara komprehensif dalam konteks sistem akuntansi modern masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis bentuk integrasi AI dan ESG dalam sistem akuntansi modern serta perannya dalam meningkatkan kualitas pelaporan keberlanjutan perusahaan. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan tinjauan pustaka (literature review) terhadap 20 artikel jurnal ilmiah bereputasi yang diterbitkan pada periode 2021–2025. Sumber literatur diperoleh dari berbagai basis data akademik, meliputi Google Scholar, ScienceDirect, SSRN, dan ResearchGate, guna memastikan keluasan dan kedalaman kajian. Analisis data dilakukan menggunakan analisis isi (content analysis) dengan mengelompokkan temuan penelitian ke dalam tema-tema utama terkait penerapan AI dalam pelaporan ESG, akuntansi karbon, serta tata kelola dan etika AI. Hasil penelitian menunjukkan bahwa integrasi AI dalam sistem akuntansi berkontribusi pada peningkatan efisiensi proses pelaporan, akurasi dan ketepatan waktu data keberlanjutan, serta transparansi informasi ESG melalui otomatisasi pengumpulan dan pengolahan data, analisis risiko, dan dukungan pengambilan keputusan. Penelitian ini menyimpulkan bahwa integrasi AI dan ESG memperluas peran sistem akuntansi dari sekadar alat pencatatan keuangan menjadi instrumen strategis dalam mendukung akuntabilitas dan keberlanjutan perusahaan.